Application of industrial by‑product waste as soil stabilising backfill material using a multi‑layering method - Al Jaber, Maryam; Nurmunira, Muhammad; Selvaraj, Jeevanraj (Springer Nature, 2024)
Peat soil presents significant challenges for construction due to its inherent weak properties, including high water content, limited permeability, low shear Strength, low specific gravity, and acidity. Despite the potential of Mg-rich synthetic gypsum (MRSG) to improve soil properties, research on its use for stabilising severely poor peat soils is limited. This study addresses this gap by investigating the efficacy of MRSG in peat soil stabilisation using a novel multi-layering backfill approach. The methodology includes soil classification of peat soil. And, to understand the mechanical and chemical changes of stabilized peat soil, the unconfined compressive Strength (UCS) testing and microstructural analysis using SEM, EDX, and XRD before and after stabilisation are studied. Peat samples were treated with MRSG through backfilling method in 5, 7, and 9 layers and evaluated the strength increment after curing periods of 7, 28, and 60 days. Results demonstrate that MRSG significantly enhanced the compressive strength, increasing it to 210.33 kPa as early as 7 days for 9 layers of backfill incomparable with the untreated soil strength of 51.87 kPa. The new cementitious product in the soil known as ettringite was observed from SEM analysis and confirmed by the EDX and XRD analysis. By recycling industrial byproducts, this environmentally friendly method encourages sustainability and lessens dependency on raw resources, which is important for infrastructure construction and other projects in areas rich in peat.